Diversity of rotavirus strains circulating in Northern Brazil after introduction of a rotavirus vaccine: High prevalence of G3P[6] genotype. Issue 6 (17th October 2013) - da Silva Soares, Luana; de Fátima dos Santos Guerra, Sylvia; do Socorro Lima de Oliveira, Alessilva; da Silva dos Santos, Fabiola; de Fátima Costa de Menezes, Euzeni Maria; Mascarenhas, Joana d'Arc Pereira; Linhares, Alexandre C.
Abstract Rotavirus A (RVA) is the most common cause of severe acute gastroenteritis in infants and young children worldwide, causing 453, 000 deaths annually. In Brazil, the most frequent genotype identified was G1 during almost three decades in the pre‐vaccination period; however, after anti‐rotavirus vaccine introduction, there was a predominance of G2 genotype. The aim of this study was to determine the G and P genotypes of rotaviruses isolated from children under 5 years of age with acute gastroenteritis in the Northern region of Brazil, and discuss the emergence of G3P[6] genotype. A total of 783 stool specimens were obtained between January 2011 and March 2012. RVA antigen was detected in 33% (272/783) of samples using a commercial enzyme‐linked immunosorbent assay and type‐specificity was determined by reverse‐transcription polymerase chain reaction. The most common binary combination was G2P[4], representing 41% of cases, followed by G3P[6] (15%), G1P[8] (8%), G3P[8] (4%), G9P[8] (3%), and G12P[6] (2%). G3P[6] strains were analyzed further and phylogenetic analysis of VP7 gene showed that G3 strains clustered into lineage I and showed a high degree of amino acid identity with vaccine strain RV3 (95.1–95.6%). For VP4 sequences, G3P[6] clustered into lineage Ia. It was demonstrated by the first time the emergence of unusual genotype G3P[6] in the Amazon region of Brazil. This genotype shares neither VP7 nor VP4 specificity with the used vaccine and may represent a challenge to vaccination strategies. A continuous monitoring of circulating strains is therefore needed during the post‐vaccine era in Brazil. J. Med. Virol. 86:1065–1072, 2014. © 2013 Wiley Periodicals, Inc.